2009
DOI: 10.1152/ajpgi.90268.2008
|View full text |Cite
|
Sign up to set email alerts
|

Activation of guanylate cyclase C signaling pathway protects intestinal epithelial cells from acute radiation-induced apoptosis

Abstract: Uroguanylin (UGN) is a peptide hormone that binds to and activates the intestinal epithelial cell (IEC) transmembrane receptor guanylate cyclase C (GC-C), which in turn increases intracellular cGMP. Gene targeting of murine UGN or GC-C results in significantly lower levels of cGMP in IECs. On the basis of effects of cGMP in nonintestinal systems, we hypothesized that loss of GC-C activation would increase intestinal epithelial apoptosis following radiation-induced injury. We first compared apoptosis from the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 31 publications
0
41
0
1
Order By: Relevance
“…Indeed, the increased numbers of apoptotic cells previously observed in the colons of PKG2 knockout mice were localized to the luminal surface. 10 This idea is supported by a report that cGMP protects the epithelial barrier against radiation-induced damage, 12 and another showing that GCC-deficient mice have a dysfunctional intestinal barrier. 13 Although this model explains the effects of Vard in the mouse colon, we did not observe significantly increased numbers of phospho-JNK-staining cells in the colon mucosa of PKG2-deficient mice (unpublished results).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Indeed, the increased numbers of apoptotic cells previously observed in the colons of PKG2 knockout mice were localized to the luminal surface. 10 This idea is supported by a report that cGMP protects the epithelial barrier against radiation-induced damage, 12 and another showing that GCC-deficient mice have a dysfunctional intestinal barrier. 13 Although this model explains the effects of Vard in the mouse colon, we did not observe significantly increased numbers of phospho-JNK-staining cells in the colon mucosa of PKG2-deficient mice (unpublished results).…”
Section: Discussionmentioning
confidence: 87%
“…It could reflect a higher level of proliferation in the gut, but it could also be due to basal inflammation resulting from a compromised epithelial barrier as recently reported in these animals. [12][13][14] Efforts to better understand the underlying signaling remain inconclusive, largely because they have relied heavily on studies of colon cancer cells. 10,14,15 The intestinal phenotype of knockout mice deficient in various cGMP signaling components suggests that this pathway inhibits proliferation and promotes differentiation in the normal gut epithelium.…”
mentioning
confidence: 99%
“…Indeed, cGMP levels, cell migration, and apoptosis were similar in the colon of guanylin-null mice and of wild-type mice, which suggests activation of compensatory mechanisms (13). Recently, Garin-Laflam et al (14) reported that GC-C activation reduces apoptosis in intestinal epithelial cells. They observed an increased apoptotic sensitivity of intestinal epithelial cells in uroguanylin knockout mice and in GC-C knockout mice after radiation and provided evidence that cGMP is a primary downstream mediator of GC-C activation in protecting the enterocyte from radiationinduced apoptosis.…”
mentioning
confidence: 90%
“…Enhanced apoptosis was also reported in IECs of GC-C À/À mice and, as with proliferation, the effect of loss of GC-C was more profound in the small bowel as compared to the colon [65]. Recent work by our group has shown that GC-C signaling plays a role in proliferation and cellular resistance to radiation and chemical stress [68,69]. Gn À/À mice have mildly enhanced IEC proliferation and migration [70].…”
Section: Intestinal Transmembrane Guanylate Cyclase Receptors: Intestmentioning
confidence: 76%
“…Gn À/À mice have mildly enhanced IEC proliferation and migration [70]. Consistent with a role for GC-C in maintaining genomic integrity and DNA damage response, mice lacking GC-C or Ugn are susceptible to radiation-induced small bowel injury as measured by IEC apoptosis and this phenotype can be reversed by oral supplementation of cGMP [68]. Furthermore, GC-C expression is induced in injured liver and is required for hepatocyte protection following chemical damage [69].…”
Section: Intestinal Transmembrane Guanylate Cyclase Receptors: Intestmentioning
confidence: 86%